1994
DOI: 10.1177/000841749406100403
|View full text |Cite
|
Sign up to set email alerts
|

Pilot Testing of the Canadian Occupational Performance Measure: Clinical and Measurement Issues

Abstract: The Canadian Occupational Performance Measure (COPM) is a measure of a client's self-perception of occupational performance in the areas of self-care, productivity and leisure. The COPM is administered using a semi-structured interview in which the client identifies significant issues in daily activities which are causing difficulty. Extensive pilot testing of the COPM has been completed with 268 clients in communities across Canada and in New Zealand, Greece and Britain. Results indicate the COPM has a median… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
164
0
3

Year Published

2004
2004
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 238 publications
(170 citation statements)
references
References 1 publication
3
164
0
3
Order By: Relevance
“…Significant correlations have also been found in other studies for the changes in scores [17,22,56] and for the scores at the initial assessment and at the reassessment [23,26]. A possible reason for the significant correlations is that clients have difficulty interpreting the difference between the concepts of performance and satisfaction.…”
Section: Discussionmentioning
confidence: 51%
See 1 more Smart Citation
“…Significant correlations have also been found in other studies for the changes in scores [17,22,56] and for the scores at the initial assessment and at the reassessment [23,26]. A possible reason for the significant correlations is that clients have difficulty interpreting the difference between the concepts of performance and satisfaction.…”
Section: Discussionmentioning
confidence: 51%
“…Supportive evidence was found for the content, convergent, and divergent validities of the COPM [2,7,9,11,[13][14][15][16][17][18]. Clinical utility, evaluated in a number of different studies, supported the use of the COPM for a variety of clients in different settings [13,17,[19][20][21][22][23][24][25][26]. The COPM is designed to not only identify the client's perceived problems but also determine whether these problems have changed over time.…”
Section: Introductionmentioning
confidence: 99%
“…Study results demonstrated that all outcome variables (PTSD symptoms, depression symptoms, occupational performance, and satisfaction with occupational performance) significantly improved over the course of residential treatment. Furthermore, reductions in all outcome variables were clinically significant as reflected in CAPS score changes of ³15 and PCL-S score changes of ³10 (Monson et al, 2006), BDI-II average score changes from severe (29-63) to mild (14-19) depression (Beck et al, 1996), and changes in COPM levels of ³2 (Law et al, 1994;Phipps & Richardson, 2007). In sum, changes were both statistically significant and clinically meaningful.…”
Section: Discussionmentioning
confidence: 86%
“…The total performance (COPM-P) and total satisfaction (COPM-S) ratings are calculated by summing individual performance and satisfaction ratings and dividing by the total number of problems. Change in performance and satisfaction is measured by the difference in total scores over a period of time (Law et al, 1994;Phipps & Richardson, 2007). The COPM has sound construct and criterion validity and test-retest reliability of >.80 (Law et al, 1994(Law et al, , 2005McColl, Paterson, Davies, Doubt, & Law, 2000).…”
Section: Instrumentsmentioning
confidence: 99%
“…8 The COPM has demonstrated test-retest reliability (r ¼ 0.80 for performance and r ¼ 0.89 for satisfaction; ICC ¼ 0.92 for performance and ICC ¼ 0.90 for satisfaction) 8,13,14 and has been shown to be a valid measure across diagnostic categories and treatment settings. [15][16][17][18][19][20] Client-centred assessment in SCI C Donnelly et al…”
Section: Canadian Occupational Performance Measurementioning
confidence: 99%